Luminescent lanthanide metal–organic framework nanoprobes: from fundamentals to bioapplications. Issue 28 (9th July 2020) - Li, Xingjun; Lu, Shan; Tu, Datao; Zheng, Wei; Chen, Xueyuan
Abstract : This minireview summarizes the recent advances in the emerging field of luminescent Ln-MOF nanoprobes, covering from fundamental insights to bioapplications. Abstract : Metal–organic frameworks (MOFs), a unique type of porous material characterized by high porosity, large internal surface area and remarkable structural tunability, have emerged as very attractive functional materials for a variety of applications. As a promising subclass of MOFs, lanthanide metal–organic frameworks (Ln-MOFs) integrate the unique advantages of MOFs and the intrinsic features of lanthanide ions, such as sharp emission bands, long luminescent lifetimes, large Stokes shifts, high color purity and high resistance to photobleaching. In this minireview, we provide a brief overview of the most recent advances in luminescent Ln-MOF nanoprobes, which covers from their chemical and physical fundamentals to bioapplications, including their synthetic strategies, optical properties and promising bioapplications in biodetection, bioimaging and therapy. Finally, some of the most important emerging trends and future efforts toward this rapidly evolving field are also envisioned.